A 24 GHz dual FMCW radar to improve target detection for automotive radar applications. (2018) - Nguyen, Quang Ngoc; Park, Myoung Yeol; Kim, Young Su; Bien, Franklin
A 24 GHz automotive radar with dual frequency modulated continuous waveform (FMCW) is proposed. By using this modulation waveform, the ghost targets can be avoided, especially in multi-target situations. Thus, the detection ability of radar systems can be significantly improved. In this paper, in order to generate the dual FMCW signal, a dual FMCW modulation control logic (DFMCL) is proposed. This block incorporates a 24 GHz fractional-N phase locked loop (PLL), synthesise 24 GHz modulation waveform. The proposed architecture was designed using 130 nm CMOS process. Two alternative chirps of 12 ms and 6 ms were generated in the coherent processing interval. The modulation bandwidth was 200 MHz. Moreover, a radar transceiver, which consists of 24 GHz dual FMCW generator and monolithic microwave integrated circuits (MMICs), was accomplished. A behavioural simulation was conducted to evaluate the operation of the proposed generator. Then, the transceiver was modelled for testing the detection ability of the automotive radar. The results demonstrated that the proposed scheme has the ability to realise the Dual FMCW waveform for automotive radar systems. Furthermore, the system can avoid the ghost targets in multi-target scenarios.